Sosialisasi dan Pengenalan Sistem Informasi PORTAL bagi Dosen Universitas Muhammadiyah Jambi - Dani, Rian; Susanto, Dedi; Irmanelly; Novia, Tri Meli; Yunaida, Ari (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
This Community Service Activity (PKM) took place at the University of Muhammadiyah Jambi. This PKM activity aims to provide an introduction to the PORTAL application. Participants in this PKM activity are lecturers at the University of Muhammadiyah Jambi. The introduction to the PORTAL application socialization activity began with an introduction to what the PORTAL Application is and how to operate it. The introduction was carried out by providing direct examples of operating the application starting from logging into the application and what things can be accessed through the PORTAL application, things that can be accessed through the PORTAL application are doing Attendance, Teaching Schedules and Academic Advisors. This activity was welcomed positively if you see the feedback from the Lecturers who were active in asking what they did not understand and what obstacles occurred during the practice of operating the PORTAL application.